Modelling the influence of Tidal Energy Converters on sediment dynamics in Banks Strait, Tasmania. (April 2022) - Auguste, Christelle; Nader, Jean-Roch; Marsh, Philip; Penesis, Irene; Cossu, Remo
Abstract: As the tidal energy industry grows, developers are interested in the influence that large scale arrays might have on their surrounding environment including hydrodynamic and sediment. Understanding of local and regional sediment dynamics is an important element for environment impact and site assessments, as changes in sediment processes could alter bed ecosystems. In Australia, the Banks Strait located in the Northeast of Tasmania has been identified as a promising site for tidal energy. Very large sand waves have been observed near the area suitable for tidal turbines installation and they may interfere with human activities. Building from previous work, a 2D regional scale model investigated the influence of different tidal farms on the morphology of Banks Strait and especially the sand waves. Results showed that tidal farm of more than 49 MW rated power will alter the circulation of residual currents in Banks Strait leading to significant changes in the sediment dynamics, and farms less than 24.5 MW will have negligible influence on the migration of sand waves. Highlights: Morphological impact assessment of Banks Strait with tidal farms. Hydrodynamic and morphodynamic models including wave forcing are used due to the wave-current interaction in Banks Strait. Tidal farms less than 24.5 MW (rated power) have negligible influence on the migration of sand waves.